2022
DOI: 10.3389/fonc.2021.811941
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Induced Proliferation Is Attenuated by Transforming Growth Factor-β-Induced Signaling in Human Hepatocellular Carcinoma Cells

Abstract: Hepatocellular carcinoma (HCC) is often associated with an inflammatory setting. A plethora of cytokines are secreted in this milieu, actively contributing to the progression of the disease; however, the extent of cytokine interaction and how it contributes to HCC development remains an enigma. In this regard, our analysis of available patient-derived data suggests that cytokines like interleukin-6 (IL-6) and transforming growth factor-beta (TGF-β) are enriched in HCC. We further analyzed the effect of these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 72 publications
1
6
0
Order By: Relevance
“…To check the effects of IL‐6 in inducing cell viability, CCK‐8 assay was used for measuring cell viability after IL‐6 treatment. Agreeing with previous works, 18,27 cells treated with IL‐6 gradually manifested higher viability than those without IL‐6 treatment at 48 h ( p < 0.001; Figure 1B). Higher proliferative activities require quicker energy metabolism, that is, faster consumption of oxygen and energy, a signature behaviour of cancer cells 28 .…”
Section: Resultssupporting
confidence: 90%
“…To check the effects of IL‐6 in inducing cell viability, CCK‐8 assay was used for measuring cell viability after IL‐6 treatment. Agreeing with previous works, 18,27 cells treated with IL‐6 gradually manifested higher viability than those without IL‐6 treatment at 48 h ( p < 0.001; Figure 1B). Higher proliferative activities require quicker energy metabolism, that is, faster consumption of oxygen and energy, a signature behaviour of cancer cells 28 .…”
Section: Resultssupporting
confidence: 90%
“…Such conclusions are promising, when the obtained results are compared also to the activation of pro‐inflammatory genes expression IL6 and IL8 (Figures 7–9). Used gene IL6, known also as markers of proliferation, survival and migration process 54 are much elevated in healthy bronchial cells, BEAS‐2B with even any expression in cancer A549 and H1299 cells (Figures 7–9). On the other side, the expression of pro‐inflammatory marker IL8, especially in lung diseases 55 is activated after LC derivative addition to the both cancer cell lines (Figures 8 and 9).…”
Section: Resultsmentioning
confidence: 99%
“…Binding of that cytokine to its receptor (IL-6R) produces a set of complicated signals which were proven to be tumor enhancement. Furthermore, it was shown that IL-6 exposure could lead to an increase in the expression of IL-6R, potentially leading in a feedback loop that amplifies the IL-6-induced impact [ 39 ].…”
Section: Discussionmentioning
confidence: 99%